OP0126 Secreted 14-3-3E : Discovery by Proteomics of a New Subchondral Bone Mediator Involved in Cartilage Degradation During Osteoarthritis. (23rd January 2014) - Priam, S.; Bougault, C.; Gosset, M.; Houard, X.; Sellam, J.; Berenbaum, F.; Jacques, C.
Abstract : Background: Osteoarthritis (OA) is characterized by joint degeneration, leading to a progressive loss of articular cartilage in response to mechanical and biochemical factors. However, OA is a complex disease not limited to cartilage degeneration. Indeed, several experiments suggest that subchondral bone remodeling could initiate and/or contribute to cartilage loss in OA through a bone/cartilage interplay. Objectives: We aimed to identify soluble mediators released by loaded osteoblasts/osteocytes that could induce the release of pro-catabolic factors by chondrocytes by using a novel and unique bone/cartilage communication model. Methods: Murine experiments: Thanks to a three dimensional culture model, murine osteoblasts were submitted to compression in Biopress Flexercell plates. Conditioned media from compressed (CM) or uncompressed (UCM) osteoblasts were used to stimulate mouse articular chondrocytes. Then, soluble mediators released by compressed osteoblasts were identified by iTRAQ®, a differential secretomic analysis approach. Chondrocyte expression of metalloproteinases MMP-3, MMP-13 and cartilage extracellular matrix components type II collagen and aggrecan were assessed by RT-PCR, western blot analysis and ELISA. Immunodepletion and blocking antibody experiments were realized using mouse compressed conditioned media. Human experiments: OA tissue was obtained from patients undergoing total knee replacement. Subchondral bone and cartilage from tibial plateaus and femoral condyles were isolated, cut into small pieces, washed and incubated in culture medium. Conditioned media were then used to stimulate human articular chondrocytes. Results: Media from compressed osteoblast (CM) strongly induced MMP-3 and -13 chondrocyte mRNA expression. Consistently, CM osteoblasts-derived media also significantly stimulated the releases of MMP-3 and -13 by chondrocytes. CM osteoblasts-derived media also affected cartilage matrix proteins expressions by downregulating type II collagen mRNA. So, the ability of soluble mediators released by loaded osteoblasts to induce a chondrocyte pro-catabolic phenotype was demonstrated. In order to identify osteoblast-derived soluble mediators responsible for this chondrocyte phenotype, osteoblast-derived conditioned media were analyzed by iTRAQ®. This sophisticated proteomic technique allowed identification of 105 proteins secreted by osteoblasts among which only 10% were upregulated in response to compression. Among them, secreted 14-3-3ε (s14-3-3 ε) dose-dependently induced the release of pro-catabolic factors (MMP-3, MMP-13) by mouse chondrocytes. s14-3-3ε dramatically mimicked the effects of CM osteoblasts-derived media. MMP-3 and MMP-13 chondrocyte expressions were strongly inhibited by a s14-3-3 blocking antibody or by immunodepleting s14-3-3 when added into the CM osteoblasts-derived media. Furthermore, s14-3-3ε was strongly released by human OA subchondral bone and paralleled with the increase of MMP-3 expression in these human samples. MMP-3 expression was dose-dependently stimulated by recombinant s14-3-3ε in human OA chondrocytes. Conclusions: We have identified s14-3-3ε as a novel soluble mediator, critical in the communication between subchondral bone and cartilage, that opens new perspectives in the fields of biomarkers and therapeutical targets in osteoarthritis. Disclosure of Interest: None Declared